2011
DOI: 10.1136/bmjopen-2011-000303
|View full text |Cite
|
Sign up to set email alerts
|

Use and usefulness of guidelines for sickness certification: results from a national survey of all general practitioners in Sweden

Abstract: ObjectivesDiagnoses-specific sickness certification guidelines were recently introduced in Sweden. The aim of this study was to investigate to which extent general practitioners (GPs) used these guidelines and how useful they found them, 1 year after introduction.DesignA cross-sectional questionnaire study. A comprehensive questionnaire about sickness certification practices in 2008 was sent to all physicians living and working in Sweden (n=36 898, response rate 60.6%). In all, 19.7% (n=4394) of the responders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 31 publications
3
23
0
Order By: Relevance
“…A request for an active participating patient in order to manage sickness certifications was identified, which agrees with the guidelines [27]. While patients own understanding of the need for sick leave guided the physician regarding sickness certification before the guidelines [21], our findings suggest that physicians today use the guidelines to communicate with patients, which is in line with a recently published study [30]. However, we also found that physicians sometimes do not fully trust their patients.…”
Section: Handling Sickness Certificationssupporting
confidence: 81%
See 1 more Smart Citation
“…A request for an active participating patient in order to manage sickness certifications was identified, which agrees with the guidelines [27]. While patients own understanding of the need for sick leave guided the physician regarding sickness certification before the guidelines [21], our findings suggest that physicians today use the guidelines to communicate with patients, which is in line with a recently published study [30]. However, we also found that physicians sometimes do not fully trust their patients.…”
Section: Handling Sickness Certificationssupporting
confidence: 81%
“…The general principles include recommendations regarding required documentation in sickness certificates, the assessment of work ability as a tool for intervention, patient participation, early commitment, contact with the workplace, and assessing functioning and work ability related to work demands and possible work modifications [27]. Recent surveys conducted in Sweden showed that a majority of physicians perceive the guidelines as being useful, primarily in communication with patients [30]; however, physicians still experience work ability assessments as being difficult [31]. In the United Kingdom, sharing the sickness certification responsibility is part of the fitness for work initiative, which aims to develop the roles of the key members of the PHC team [28] and the NICE guidance on long-term sick leave provides opportunities for other healthcare professionals to assist in early return to work [32].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, 20–60% of the individuals, depending on the trajectory groups, did not receive any specialized mental healthcare during 3 years prior to DP. This is not in accordance with the Swedish sick-leave guidelines [54], stating that all patients on sickness absence due to depression for more than 6 months, should be referred to a specialist. This may indicate that these individuals might have not received optimal treatment during the pre-DP years, leading to further worsening of work capacity and later resulting in exclusion from the labour market by being granted DP [16].…”
Section: Discussionmentioning
confidence: 86%
“…The recommendation is 3 weeks of sick leave after breast conserving and sentinel node surgery and up to 6 weeks after mastectomy or extended axillary clearance [5], depending on the work demands of the specific work the woman has. During postoperative chemotherapy, work capacity is often reduced and sickness absence for this time period is suggested, although radiation therapy and hormonal treatment more seldom result in reduced work capacity requiring full time sick leave [5,6]. The Board of Health and Welfare has stated that sickness certification is an active measure equivalent to other healthcare recommendations and treatments and that the sickness certification should be combined with support and advice in order for the individual to be able to use their work capacity (if any) despite limitations.…”
Section: Introductionmentioning
confidence: 99%